Evaluation of Therapeutic Potential of Yoga Practice in Managing Hypertension Based on Cardiopulmonary Efficiency and Physical Fitness - Ruchi Kothari; Ashay Gomashe; Bala C. Bethamcherla; Nithila Sivakumar; Lakshiya Ramamoorthy; Lakshmi Murugesan (Journal of Pharmacy and Bioallied Sciences)
Background: Noncommunicable diseases have surged because of urbanization and prosperity, with physical inactivity increasing hypertension risk. Hypertension leads to early morbidity and mortality. Yoga, an ancient Indian practice, enhances physical, mental, and spiritual well-being through postures, breathing exercises, and meditation. This study examines yoga’s potential to lower blood pressure by increasing VO2 Max, a critical cardiovascular fitness indicator. Methods: This study involved 250 hypertension patients (systolic BP >140 mm Hg or diastolic BP >90 mm Hg) from a rural hospital. Conducted over eight months at a rural medical college’s Sports Physiology Laboratory, the study reassessed participants’ cardiorespiratory fitness after six months of yoga therapy. Data were collected using the Metabolic module of the Exercise Physiology System and Power Lab System with LabChart Pro software. Results: VO2 Max for males improved significantly from 23.1 ± 10.02 mL/min/kg to 28.5 ± 9.85 mL/min/kg (P = 0.017), and for females from 21.3 ± 3.21 mL/min/kg to 25.4 ± 4.12 mL/min/kg (P = 0.028). Detail demographic data, blood pressure, VO2 Max, and BMI changes before and after yoga therapy. Conclusion: The study highlights yoga’s potential in managing hypertension, showing significant improvements in VO2 Max, blood pressure, and BMI, supporting yoga as an effective therapeutic intervention.